Influence of Human And Spatial Crowding On Consumer Satisfaction Through Attractiveness As A Mediation Variable In Noodle Restaurant - Kasana, Tiara Miladiyatul; Setiawan, Budi; Shinta, Agustina; Ilsan, Mais (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2025)
The development of the culinary business, particularly in spicy noodle restaurant is increasing the popularity among the public. However, crowding in restaurant can directly influence consumer satisfaction. Therefore, this research aimed to (1) analyze influence of human and spatial crowding on consumer satisfaction and attractiveness, (2) assess the impact of attractiveness on consumer satisfaction, and (3) examine influence of human and spatial crowding on consumer satisfaction through attractiveness as a mediating variable. A quantitative research method was used, while the samples were determined using a judgment sampling technique, yielding a total of 100 respondents. Data were collected primarily using a closed questionnaire. Subsequently, data analysis was carried out using descriptive statistical and SEM-PLS analysis with the WarpPLS 8.0 analysis tool. The results showed that (1) human and spatial crowding had a positive and significant influence on consumer satisfaction and attractiveness, (2) attractiveness had a positive and significant influence on consumer satisfaction, and (3) human and spatial crowding had a positive and significant influence on consumer satisfaction through attractiveness as a mediating variable.